2021
DOI: 10.1111/cdev.13609
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Depressive Symptoms and Children’s Internalizing and Externalizing Behaviors: Examining Reciprocal Trait‐State Effects from Age 2 to 15

Abstract: Using a large sample from the National Institute of Child Health and Development Study of Early Child Care and Youth Development (N = 1,178, 51% were male and 80% were White), the random intercept cross-lagged panel model was employed to unpack the trait and state aspects in the relations between mothers' depressive symptoms and children's behavioral problems from age 2 to 15. The transactional predictions among mothers' depressive symptoms and children's behavioral problems were largely attributed to their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 48 publications
3
16
1
Order By: Relevance
“…A growing body of studies has adopted a family systems perspective in which each family member influences, and is influenced by, others in the same family (Cox & Paley, 2003; Minuchin, 1985); incorporated theories that recognize adolescents as active shapers of their environment, rather than passive recipients of environmental influences (e.g., transactional model of development by Sameroff, 2009; interpersonal models of depression by Coyne, 1976); and empirically tested a transactional model of depression, in which parental depression and adolescent depression affect one another reciprocally. To our knowledge, only a handful of studies tested the transactional model of depression with a repeated-measure design, yielding highly mixed findings for reasons including differences in analytic approaches and heterogeneity in sample sources (e.g., convenient sample, clinical sample, community sample; see Ge et al, 1995; Griffith et al, 2021; Hughes & Gullone, 2010; Mennen et al, 2018; Sellers et al, 2016; Yan et al, 2021). Applying the traditional cross-lagged panel model (CLPM), several studies found evidence of reciprocity between adolescent and parental depression (Ge et al, 1995; Hughes & Gullone, 2010; Mennen et al, 2018).…”
Section: Familial Transmission Of Depression: a Tale Of Mixed Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of studies has adopted a family systems perspective in which each family member influences, and is influenced by, others in the same family (Cox & Paley, 2003; Minuchin, 1985); incorporated theories that recognize adolescents as active shapers of their environment, rather than passive recipients of environmental influences (e.g., transactional model of development by Sameroff, 2009; interpersonal models of depression by Coyne, 1976); and empirically tested a transactional model of depression, in which parental depression and adolescent depression affect one another reciprocally. To our knowledge, only a handful of studies tested the transactional model of depression with a repeated-measure design, yielding highly mixed findings for reasons including differences in analytic approaches and heterogeneity in sample sources (e.g., convenient sample, clinical sample, community sample; see Ge et al, 1995; Griffith et al, 2021; Hughes & Gullone, 2010; Mennen et al, 2018; Sellers et al, 2016; Yan et al, 2021). Applying the traditional cross-lagged panel model (CLPM), several studies found evidence of reciprocity between adolescent and parental depression (Ge et al, 1995; Hughes & Gullone, 2010; Mennen et al, 2018).…”
Section: Familial Transmission Of Depression: a Tale Of Mixed Evidencementioning
confidence: 99%
“…True development manifests within people across time, and the RI-CLPM is able to capture this within-person change, making it better to assess development and change while also capturing between-person trait-like effects. Given the considerable trait-like aspects of depression shaped by not only genetics (Goodman & Gotlib, 1999) but also by the often-stable contextual factors (e.g., family socioeconomic status [SES]; Yan et al, 2021), the failure to disentangle between- and within-person/family sources of variance may represent a salient methodological issue in the inquiries of familial clustering of depression. To our knowledge, two recent studies applied the RI-CLPM to properly disaggregate between-family and within-family effects and investigated the reciprocal within-family effects between adolescent and parental depression, both drawing samples consisting of predominantly white participants (Griffith et al, 2021; Yan et al, 2021).…”
Section: Familial Transmission Of Depression: a Tale Of Mixed Evidencementioning
confidence: 99%
“…(2019) found that externalizing problems mostly predicted internalizing problems among children between 3 and 14 years. Another recent study utilizing RI‐CLPM found significant concurrent correlations between internalizing and externalizing problems at the within‐person level and a positive association from third grade internalizing problems to fifth grade externalizing problems (Yan et al., 2021). As these studies also discuss, it is important to distinguish within‐ and between‐person processes to have less biased results and to be able to examine the co‐development of internalizing and externalizing problems (Murray et al., 2020; Yan et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study utilizing RI‐CLPM found significant concurrent correlations between internalizing and externalizing problems at the within‐person level and a positive association from third grade internalizing problems to fifth grade externalizing problems (Yan et al., 2021). As these studies also discuss, it is important to distinguish within‐ and between‐person processes to have less biased results and to be able to examine the co‐development of internalizing and externalizing problems (Murray et al., 2020; Yan et al., 2021). The transition from early childhood to early adolescence is important for the development of peer relationships and social skills that are related closely to psychological adjustment in children (Ladd & Troop‐Gordon, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation